Penetapan Nilai Jual Objek Pajak yang Berimplikasi pada Penerimaan PBB-P2 Kota Cilegon Tahun 2014-2018 - Devi, Deasy Femayona (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2023)
The purpose of this study was to determine the determination of the sale value of tax objects as the basis for the imposition of PBB-P2 at the City of Cilegon, the level of effectiveness and contribution of the receipt PBB-P2 at the City of Cilegon, the factors can hamper the receipt of PBB-P2 at the City of Cilegon and efforts that can optimize the  revenue PBB-P2. The method used in this research is descriptive qualitative method. The results showed that the Determination of the Sales Value of Tax Objects as the basis for the imposition of PBB-P2 in the City of Cilegon used a price comparison method which was conducted once a year. The level of effectiveness PBB-P2 in the city of Cilegon in 2014-2018  very effective,  And the contribution of PBB-P2 in the city of Cilegon is still in the category of under-contributing the Regional Original Revenue.